The relative age effect among elite American youth soccer players - Glamser, F. D.; Vincent, J. (Journal of Sport Behavior, 2004)
Children are frequently grouped by age for school or sport activities in order to control for the effects of intellectual and physical development. However, even when groupings are limited to 1 -year categories, developmental differences can be great (DeMeis & Stearns, 1992). In such cases, some children will be almost a year older than other children. The outcome of this advantage has been termed the relative age effect (RAE) or the birth date effect.